Systemic-Functional Approach to Utilities Supplys - Nikolay I. Komkov; Taliya Kh. Usmanova; Dmitry A. Isakov (Модернизация, инновация, развитие)
Purpose: the purpose of the article consists in statement of management approach to development of utilities supply processes based on conflict situations decision – making search. It had appeared in the period of the transition from the planned and directive management to market development. Methods: the research methodology is based on the system analysis of full life cycle processes functioning, forecasting of complex systems development, mathematical modeling of processes of services supply and innovative and investment projects modeling as well as development of supplying services processes. Results: the results of the work are concentrated in the presentation of systemic-functional approach to managing the development of processes of municipal services, able to resolve conflict situations in this sphere. Conclusions and Relevance: the traditional management approach on the basis of elimination of "bottlenecks" and emergencies prevailing within planned and directive system at its transformation in the market conditions has led to accumulation of conflict situations and unsolvable problems. The offered systemic-functional approach based on forecasting of full life cycle of the modernized processes and the services providing systems allows to consider costs of modernization, prime cost and quality of the rendered services.